Rational Tuning of Molecular Interaction and Energy Level Alignment Enables High‐Performance Organic Photovoltaics. Issue 43 (9th September 2019) - Wang, Rui; Yuan, Jun; Wang, Rui; Han, Guangchao; Huang, Tianyi; Huang, Wenchao; Xue, Jingjing; Wang, Hao‐Cheng; Zhang, Chunfeng; Zhu, Chenhui; Cheng, Pei; Meng, Dong; et al.
Abstract: The performance of organic photovoltaics (OPVs) has rapidly improved over the past years. Recent work in material design has primarily focused on developing near‐infrared nonfullerene acceptors with broadening absorption that pair with commercialized donor polymers; in the meanwhile, the influence of the morphology of the blend film and the energy level alignment on the efficiency of charge separation needs to be synthetically considered. Herein, the selection rule of the donor/acceptor blend is demonstrated by rationally considering the molecular interaction and energy level alignment, and highly efficient OPV devices using both‐fluorinated or both‐nonfluorinated donor/acceptor blends are realized. With the enlarged absorption, ideal morphology, and efficient charge transfer, the devices based on the PBDB‐T‐F/Y1‐4F blend and PBDB‐T‐F/Y6 exhibit champion power conversion efficiencies as high as 14.8% and 15.9%, respectively. Abstract : By rationally tuning the molecular interaction and energy level alignments of the donors and acceptors, when both donor and acceptor are fluorinated or both are not fluorinated, high‐performance organic photovoltaics can be realized. With the enlarged absorption, ideal morphology, and efficient charge transfer, devices based on the PBDB‐T‐F/Y1‐4F blend and PBDB‐T‐F/Y6 exhibit power conversion efficiencies as high as 14.8% and 15.9%, respectively.